Penetration of different molecule sizes upon ultrasound combined with microbubbles in a superficial tumour model. (26th November 2019) - Wei, Yingli; Shang, Ning; Jin, Hai; He, Yan; Pan, Yuwei; Xiao, Nina; Wei, Jinglu; Xiao, Shuyi; Chen, Liping; Liu, Jianhua
Abstract: Ultrasound combined with microbubbles (USMB) has been extensively applied to enhance drug and gene targeting delivery. However, the accumulation and distribution of particle size in the range of 5–30 nm (nano drug) to the tumour and the effects of intratumoral vascular density on permeability have been rarely reported. This study investigated Evans blue (EB) and fluorescein isothiocyanate-labelled dextran (FITC-dextran) distribution in tumour tissue upon USMB with various molecular sizes (3.7 nm and 30.6 nm). USMB increased the penetration of molecules with sizes of 5-20 nm in the whole tumour tissue, especially on the rim. For a molecule with sizes of 30.6 nm, USMB only increased penetration around the rim of the tumour with minimal improvement in the central of tumour. USMB enhanced the permeability of tumour tissue and increased tumour cells dose exposure without affecting tumour blood perfusion or microvessel density. The current study served as the foundation of parameter preference for therapeutic USMB drug delivery.